Oncogenic RAS Networks Suppression: Reversibly Ionic Oligonucleotide‐Based Nanoparticles Caged microRNA‐143 Inhibit KRAS‐Mutated Colon Cancer Growth in Tumor‐Bearing Mice. Issue 2 (17th November 2022) - Miyamoto, Noriko; Kawasaki, Riku; Sakuragi, Mina; Yamana, Keita; Isozaki, Hinata; Kawamura, Shogo; Akiba, Isamu; Kitade, Yukio
Abstract: Oncogenic RAS has been a particular focus of attention as a pharmacological target over the last four decades. Tumor‐suppressor microRNA‐143 (miR‐143) silences oncogenic KRAS networks, but it requires a nucleic acid delivery vehicle for clinical application. DNA‐ or RNA‐based nucleic acid structures (NASs) are attractive as vehicles that can form unique sequence‐based structures. However, for the biological application of NASs, it is still challenging to create a nanostructure that is stable under physiological conditions by reducing intramolecular repulsion due to negative charges. Here, a novel NAS (named RION miR‐143 : reversibly ionic oligonucleotide‐based nanoparticles caged miR‐143) is created by self‐assembly involving hybridization and electrostatic interaction via chemically modified oppositely charged ion oligonucleotides. RION miR‐143 are nanoparticles of about 70 nm in diameter with improved nuclease resistance under physiological conditions. Moreover, RION miR‐143 inhibit the expression of proteins in KRAS networks and cell growth in a dose‐dependent manner in KRAS‐mutated DLD‐1 cells. The anti‐tumor activity of RION miR‐143 is demonstrated in a DLD‐1 cell‐bearing mouse model, with a fourfold decrease in tumor volume compared with Naked miR‐143 . This report presents RION miR‐143 as a new option for oncogenic KRAS‐targeting medicine, which can be used as a potent nucleic acid delivery platform. Abstract : This manuscript reports a novel therapeutic strategy for RAS‐mutated intractable cancers. Tumor‐suppressor microRNA‐143 (miR‐143) silences oncogenic KRAS networks, but it lacks a nucleic acid delivery vehicle for clinical application. This research creates a novel delivery vehicle (named RION miR‐143 ) by self‐assembly of miR‐143s and demonstrates delivery functions without delivery reagents such as a lipid nanoparticle.